Monitoring Atmospheric Aerosols Over the Urmia Lake by CALIPSO and a Ground Based Depolarized Lidar - Khalesifard Hamid R.; Panahifar Hossein; Ghomashi Fatemeh; Alizadeh Salar; Moradhaseli Ruhollah (EPJ Web of Conferences, 2020)
The Urmia Lake, a hypersaline lake in Northwest Iran is facing a severe drying scenario. We have installed an azimuthal scanning depolarized backscatter lidar in the coast of the lake to monitor the atmospheric aerosols that may originate from the dried lake bed. We also used the CALIPSO recordings to monitor the aerosol optical depth and particulate depolarization ratio just over the lake. Recordings of the lidar and CALIPSO both show that dry salt particles can be found in the atmospheric boundary layer over the lake especially in summer times. Also CALIPSO data in synergy with HYSPLIT model show that the lake is not an intense aerosol source comparing to neighboring sources like the Mesopotamia region but it is under their influence.